Revision of the genera Pseudotraulia Laosinchai & Jago, 1980 and Bannacris Zheng, 1980 (Orthoptera: Acrididae) with proposal of new synonyms - Storozhenko, Sergey Yu.; Mao, Benyong; Dawwrueng, Pattarawich; Taekul, Charuwat; Willemse, Luc; Huang, Jianhua (European Journal of Taxonomy, 2022)
The genera Pseudotraulia Laosinchai & Jago, 1980 and Bannacris Zheng, 1980 are revised based on the examination of types and additional materials. Bannacris punctonotus Zheng, 1980 is synonymized with Pseudotraulia cornuata Laosinchai & Jago, 1980 and Bannacris Zheng, 1980 with Pseudotraulia Laosinchai & Jago, 1980. The tribal placement of Pseudotraulia is discussed and the genus Pseudotraulia is transferred here from the tribe Mesambriini of the subfamily Catantopinae Brunner von Wattenwyl, 1893 to the subfamily Coptacrinae Brunner von Wattenwyl, 1893 which is not divided into tribes and consists of 22 genera distributed in the Afrotropical and Oriental regions.